2022
DOI: 10.1038/s41467-022-31142-5
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell profiling of the antigen-specific response to BNT162b2 SARS-CoV-2 RNA vaccine

Abstract: RNA-based vaccines against SARS-CoV-2 have proven critical to limiting COVID-19 disease severity and spread. Cellular mechanisms driving antigen-specific responses to these vaccines, however, remain uncertain. Here we identify and characterize antigen-specific cells and antibody responses to the RNA vaccine BNT162b2 using multiple single-cell technologies for in depth analysis of longitudinal samples from a cohort of healthy participants. Mass cytometry and unbiased machine learning pinpoint an expanding, popu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 105 publications
0
40
0
Order By: Relevance
“…Both SARS-CoV-2 infection and vaccination effectively elicited T cell and B cell responses against SARS-CoV-2 (3,16), providing a high level of protection against symptomatic SARS-CoV-2 infection (17), despite the challenges posed to the waned immunity by the immunity-escaping emerging viral variants. Of note, single-cell analysis together with the classic immunological assay, have greatly contributed to deeper understanding of the dynamics of SARS-CoV-2-specific CD4 + and CD8 + T cells, B cells and neutralizing antibodies (18)(19)(20)(21)(22)(23) during natural infection and various vaccination (Table 1) (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). A comprehensive comparison of the adaptive immune responses with natural infection and vaccination is required to dissect the protective immune properties against SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…Both SARS-CoV-2 infection and vaccination effectively elicited T cell and B cell responses against SARS-CoV-2 (3,16), providing a high level of protection against symptomatic SARS-CoV-2 infection (17), despite the challenges posed to the waned immunity by the immunity-escaping emerging viral variants. Of note, single-cell analysis together with the classic immunological assay, have greatly contributed to deeper understanding of the dynamics of SARS-CoV-2-specific CD4 + and CD8 + T cells, B cells and neutralizing antibodies (18)(19)(20)(21)(22)(23) during natural infection and various vaccination (Table 1) (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). A comprehensive comparison of the adaptive immune responses with natural infection and vaccination is required to dissect the protective immune properties against SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated increasing spike-specific B cells, antigen-specific CD4 + T cells, and CD8 + T cells by scRNA-seq analysis in healthy subjects after mRNA vaccines and those after COVID-19 infection ( 31 ). Kramer KJ and the colleagues focused on adaptive immunity and indicated enlarged population of antigen-specific memory CD4+ and CD8+ T cells, and IgA and IgG memory B cells specific to SARS-CoV-2 in healthy participants after BNT162b2 mRNA vaccines ( 32 ). Those studies highlighted the importance of antigen presentation and antibodies productions following mRNA vaccines in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“… 264 , 265 A mass cytometry‐based study identified expansion of metabolically active, class‐switched plasmablasts expressing CD71, CD98, and cytochrome C between day 0 and 28 post‐vaccine. 266 Similarly, Amanat et al 128 reported that some of the isolated S2‐specific mAbs had cross‐reactivity toward human coronaviruses, suggestive of recall responses which were initially induced by seasonal beta‐coronavirus exposure. To support this model, some of the cross‐reactive mAbs showed extensive SHM.…”
Section: Asc Responses To Sars‐cov ‐2 Vac...mentioning
confidence: 99%
“…Studies have shown that the first dose generated polyclonal non‐neutralizing IgA‐dominant ASC response with some S2‐specific plasmablasts with low SHM, whereas the second dose provided neutralizing B cell responses to S1 with RBD 264,265 . A mass cytometry‐based study identified expansion of metabolically active, class‐switched plasmablasts expressing CD71, CD98, and cytochrome C between day 0 and 28 post‐vaccine 266 . Similarly, Amanat et al 128 reported that some of the isolated S2‐specific mAbs had cross‐reactivity toward human coronaviruses, suggestive of recall responses which were initially induced by seasonal beta‐coronavirus exposure.…”
Section: Asc Responses To Sars‐cov‐2 Vaccinationmentioning
confidence: 99%